IMPLEMENTATION OF SCIENTIFIC APPROACH IN SOCIAL STUDIES SUBJECTS AT SD NEGERI 56 KOTA TERNATE: IMPLEMENTASI PENDEKATAN SAINTIFIK PADA MATA PELAJARAN IPS DI SD NEGERI 56 KOTA TERNATE - Harmoko Muhammad; Rustam Hasim; Irwan Abbas (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to analyze the implementation of the scientific approach in Social Studies (IPS) subjects at SD Negeri 56 Ternate City. The scientific approach, which includes the stages of observing, asking, collecting data, associating, and communicating, is expected to improve students' understanding of IPS material and improve critical and creative thinking skills. This study uses a qualitative method with a case study approach, involving observation, interviews, and documentation as data collection techniques. The results of the study indicate that the implementation of the scientific approach in IPS learning at SD Negeri 56 Ternate City went quite well, although there were several challenges, such as limited time and supporting facilities and infrastructure. However, this approach has been proven to stimulate students' interest and active participation in the learning process, and has a positive impact on their learning outcomes. Based on these findings, it is recommended that teachers optimize the use of the scientific approach by paying attention to the availability of adequate facilities and time to support the success of the learning process.